Removal and Recovery of Chromium from Solutions Simulating Tannery Wastewater by Strong Acid Cation Exchanger - Cetin, Gulten; Kocaoba, Sevgi; Akcin, Goksel (HINDAWI LTD, 2013)
The process in this study was conducted on removal of chromium(III) in a solution simulating a typical spent chrome tanning bath by the resin having matrix of styrene-divinylbenzene-based macroporous sulphonate, Amberjet 1200Na. The column experiments were carried out with the bed volumes of the resin as 751 mL and 1016 mL for different installation systems of the laboratory-scale pilot plant. The feeding solutions in the bed volumes of 200 and 190 were used for each installation system. The regeneration behaviour of the resin was determined by using reverse regeneration procedure with the solution of hydrogen peroxide in alkaline. The regeneration kinetics of the exhausted resin was examined with a range of the solutions having different concentration series of the alkaline hydrogen peroxide. The solutions of the basic chromium sulphate were recycled for each installation system following the regeneration cycles. The chromium ions in effluent were quantitatively eluted, and satisfactory removal of chromium(III) and recovery of chromium(VI) were achieved.
Keywords: SOLID-PHASE EXTRACTION; SPECIATION; CR(III); SLUDGE; CR(VI); RESIN; Chemistry